60GHz low noise amplifier - Neo, Kah Wei (2014)
Due to the importance of low noise amplifier in the receiver, it is been placed at the first stage of the receiver front-end. After the signal has passes through the atmosphere, it has been weaken through the air. Hence, a Low noise amplifier is placed to amplify the signal. Moreover, to provide high voltage input into the following stage known as the mixer, not only it has to provide sufficient gain and subdue the effect of noise with the following stages, it has to minimize as little noise added into the mixer. Thus, this shows the importance of a low noise amplifier. As the 60GHz is assigned worldwide for unlicensed wireless communication systems to provide short-range Wi-Fi wireless networking which speeds up to 7Gbps compared to current speed of 1Gbps using the 2.4GHz network. In this project, a Low Noise Amplifier ( LNA ) was designed and simulated using Cadence ADE L software in 65nm process as different topology is been explained and explored. Finally a topology had been employed called the 2-stage cascade topology whereby the common-source and common-drain transistors are joined together to form the first and second stage. The purpose is to explore the consumption of power, performance of noise, amount of gain, sensitivity and stability of the system and last but not least the linearity of the system. In addition, the Low Noise Amplifier achieves a gain of 9.299dB, Noise Figure of 3.924dB while drawing 3.37mA from a 1.2V supply. Therefore a moderate gain and low Noise Figure was attained with low power consumption.